Life expectations in early adolescence and the timing of first sex and marriage: evidence from a longitudinal survey in Ethiopia - David P. Lindstrom; Ida Sahlu; Tefera Belachew; Mulusew Gerbaba (Reproductive Health, 2022)
Plain Language summary Raising the median age of their first heterosexual intercourse, or first sex, and marriage for females is a policy goal of the Ethiopian government. Research in Africa has found evidence of a positive association between higher levels of completed schooling and older ages at first sex and marriage among females. A substantial body of research conducted in the United States shows that youth who develop high educational and occupational expectations at young ages also tend to delay first sex and marriage. High expectations motivate youth to stay in school longer and avoid behaviors, such as early sex and marriage, that put their goals at risk. Evidence of a similar association in Ethiopia, however, has been lacking because of the scarcity of longitudinal data. In this study, we used data from the Jimma Longitudinal Family Survey of Youth conducted in southwestern Ethiopia to examine the impact of early career expectations and marriage plans on the risk of first sex during adolescence among male and female youth and on the risk of first marriage during adolescence among females. Using discrete-time logistic hazard regression models, we found that adolescents who had high career expectations at ages 13–17 were significantly less likely to have their first sexual intercourse over the following four years. We also found that the protective effects of being in school on delaying first sex wore off with time, but the effect of high career expectations persisted. Finally, we found that parents’ desire for an older age at marriage for their daughters had a significant delaying effect on daughter’s marriage.